(untitled) (Publicaciones en Ciencias y Tecnología, 2012)
This narrative character article and written from a personal perspective, has the aim to tell the sequence of events, in terms of matematician formation programs in the center west region of the country, which leads to the oppening of the Doctorate in Mathematic Program at the Lisandro Alvarado University. Some reections about the mathematical activities at this university are also exposed.